Melanocortin therapies to resolve fibroblast-mediated diseases - Khodeneva, Natalya; Sugimoto, Michelle A.; Davan-Wetton, Camilla S. A.; Montero-Melendez, Trinidad (Frontiers in Immunology, 2023)
Stromal cells have emerged as central drivers in multiple and diverse diseases, and consequently, as potential new cellular targets for the development of novel therapeutic strategies. In this review we revise the main roles of fibroblasts, not only as structural cells but also as players and regulators of immune responses. Important aspects like fibroblast heterogeneity, functional specialization and cellular plasticity are also discussed as well as the implications that these aspects may have in disease and in the design of novel therapeutics. An extensive revision of the actions of fibroblasts on different conditions uncovers the existence of numerous diseases in which this cell type plays a pathogenic role, either due to an exacerbation of their 'structural' side, or a dysregulation of their 'immune side'. In both cases, opportunities for the development of innovative therapeutic approaches exist. In this regard, here we revise the existing evidence pointing at the melanocortin pathway as a potential new strategy for the treatment and management of diseases mediated by aberrantly activated fibroblasts, including scleroderma or rheumatoid arthritis. This evidence derives from studies involving models of in vitro primary fibroblasts, in vivo models of disease as well as ongoing human clinical trials. Melanocortin drugs, which are pro-resolving mediators, have shown ability to reduce collagen deposition, activation of myofibroblasts, reduction of pro-inflammatory mediators and reduced scar formation. Here we also discuss existing challenges, both in approaching fibroblasts as therapeutic targets, and in the development of novel melanocortin drug candidates, that may help advance the field and deliver new medicines for the management of diseases with high medical needs.